Topónimos célticos en Galicia (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this paper is to study place names that, with some ex ceptions, have not survived as common names in the Galician language and that, therefore, can be relevant for the linguistic map of Pre-Roman Gallaecia. Taking into account their word bases, derivational suffixes and comparative correspon dences in other Celtic areas, the place names I study can fit into the Celticcor pus, despite some doubts and problems in some items. I stress the frequent repetition of combinations of some roots and suffixes, for instance,Barra / Bar ranca / Barraña / Barrantes... or Caranco / Caraña / Carantoña / Carantos / Caranza / Carazo... The analysed place names concentrate in areas of Neri, Su pertamarci, Praestamarci, Copori, Artabri, Baedui, Lapatianci..., that is to say, outstanding areas in other fields of Celtic toponymy in Gallaecia.
Keywords: Celtic Toponymy; Gallaecia; Roots and Suffixes